Hubungan Intensitas Penggunaan Generative Artificial Intelligence dengan Tingkat Etika Akademik Mahasiswa PPKn FKIP Universitas Lambung Mangkurat - Adistia Adistia; Wardiani Hiliadi (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study examines the relationship between the intensity of Generative Artificial Intelligence utilization and the academic ethics of PPKn students at the Faculty of Teacher Training and Education (FKIP) of the University of Muhammadiyah Malang (UMM). This study employed a quantitative correlational approach using total sampling involving 157 respondents from the classes of 2024 and 2025. Data were collected using a Likert-scale questionnaire and then analyzed using descriptive statistics and the Spearman correlation test using SPSS version 26. The study results illustrate that the intensity of Generative Artificial Intelligence utilization among students is moderate, while academic ethics is high. The Spearman's rho coefficient value is 0.310 and a significance level of 0.000, less than 0.05, indicates a positive, significant relationship with small magnitude. This means that the higher the intensity of Generative Artificial Intelligence utilization, the higher the level of academic ethics among students. These findings indicate that Generative Artificial Intelligence, used productively and reflectively, has the potential to strengthen academic integrity.